Hitting the Reset Button: Ceremonial Use of Peyote and Experiences of Personal Change - Copes, Heith (Journal of drug issues, 2026)
Our aim is to understand how those who use peyote in a naturalistic setting discuss it changed their lives and to what they attribute this change. To do this, we draw on data from a photo-ethnography of people who attended peyote ceremonies in rural Northcentral Alabama. Broadly, we found that participants discussed four core areas of change: reduced drug and alcohol misuse, new perspectives on life, improved mental health, and improved physical health. The duration of the experienced change varied for each type of change. Participants attributed change to improved ability to endure challenges, rewiring of the brain, and connecting with spiritual selves. Findings give insights into how people experience and make sense of change from peyote. In addition, the findings suggest specific areas of research for those interested in clinical and therapeutic settings relating to peyote in particular, and psychedelics in general.